Polyculture of Machrobracium nipponense (De Haan, 1849) with Ctenopharyngodon idella Val., 1844 in laboratory conditions - Al-Maliky, T.H.Y. (Mesopotamian Journal of Marine Sciences, 2022)
The laboratory test on effect of grass carp (Ctenopharyngodon idella) at different densities in polyculture with oriental river prawn (Macrobrachium nipponense) was the aim of this study. The experiment includes three treatments, prawn and 6 grass carp m-² (T1), prawn and 8 grass carp m-² (T2) and prawn and 10 garss carp m-² (T3), with three replicates in each. The prawn stocking density was the same in all treatments (10 juvenile m-²). Feeds were applied twice daily for prawn. Feeding rates were gradually reduced to 10 - 7% of body weight from the beginning to the last month. Water quality parameters (temperature, pH, salinity and DO) did not vary significantly (P>0.05).The mean of juvenile weight in the final weights and the increasing weight and daily growth were differed significantly (P<0.05) between the treatment T1 as well as of the two treatments T2 and T3, Which had not significant differences (P>0.05). While not significant differences (P>0.05) in both survival and relative growth rates in all transactions. It was found that the addition of different grass carp did not affect on rates of both survival and relative growth of prawns, evidence favorable to store fish with prawn. It can be concluded that the treatments T3 was the best for prawn-fish polyculture.